Agile-Based Accreditation Module Design for the P3M Information System at Politeknik Negeri Samarinda - Arsan Kumala Jaya; Fara Triadi; Subhan Hartanto; Ahmad Saiful Mutaqi Azis; Priti Shinta (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
Accreditation serves as a critical quality assurance mechanism in higher education; however, manual and fragmented data management creates significant challenges in collecting accreditation documentation and reports. This research designs and develops an Accreditation Menu for the P3M Information System at Politeknik Negeri Samarinda to streamline accreditation processes with greater effectiveness, efficiency, and accountability. Using an iterative Agile Scrum methodology across five development sprints, the study implemented integrated CRUD operations, advanced search-filtering capabilities, real-time notification systems, comprehensive user acceptance testing, and Docker-based deployment. Key results demonstrate that the Accreditation Menu reduces document preparation time by 40%, improves data accuracy from 88% to 97%, and achieves 92% user satisfaction (UAT survey, n=25 stakeholders). The system successfully manages accreditation indicators, supporting documentation, and reporting in full compliance with LAM INFOKOM standards while providing real-time data integration between research activities and accreditation requirements. This work improves accreditation efficiency, reduces administrative burden, and supports institutional compliance with national quality assurance standards. The Agile approach enables rapid adaptation to evolving user needs and regulatory changes, with promising opportunities for AI-based predictive monitoring and integration with national accreditation systems.